Audio Visual Translation: Subtitling Pragmatic Features - Al-Bin-Ali, Manal Ahmed (2006)
A Master of Arts Thesis in English/Arabic Translation and Interpreting Submitted to the College of Arts and Sciences by Manal Ahmed Al-Bin-Ali Entitled, "Audio Visual Translation: Subtitling Pragmatic Features," December 2006. Available are both Soft and Hard Copies of the Thesis.